Hubungan Status Demografi, Komorbid Dengan KIPI Post Vaksin COVID-19 Pada Tenaga Kesehatan - Vera Yulyani; Neno Fitriyani Hasbie; Achmad Farich; Amelia Valentine (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Background: Health workers are potentially infected due to their exposure to COVID-19 patients during work shifts, All clinical symptoms that occur due to needle prick trauma both directly and indirectly should be recorded as a KIPI reaction. Goal: Knowing the symptoms of kipi along with related factors experienced by health workers as the forefront in fighting the current coronavirus pandemic. Method: Observational analytics using a cross sectional method approach using a total sampling technique of 155 samples overall. Data retrieval begins in November 2021. This research was conducted at Pertamina Bintang Amin Bandar Lampung Hospital. Chi-square test statistical data using SPSS 25. Result: There is no relationship between demographic status and comorbid diseases with KIPI because of the results of p-value data <0.05. Conclusion: That there is no relationship between demographic status, comorbid status and KIPI in Health Workers.